Economic Vulnerability, Entrepreneurial Competencies, and Performance of Informal Micro-Enterprises. Issue 5 (29th July 2019) - Mamun, Abdullah Al; Fazal, Syed Ali; Zainol, Noor Raihani
ABSTRACT: This study highlights the effect of economic vulnerability on entrepreneurial competencies and the performance of informal microenterprises in Kelantan, Malaysia. This study adopts a cross-sectional design, and quantitative data is collected through a structured interview of 384 randomly selected informal women microentrepreneurs. Findings confirm that economic vulnerability has a significant negative effect on commitment competency, conceptual competency, organizing competency, opportunity recognition competency, relationship competency, and the performance of informal microenterprises owned and managed by women microentrepreneurs. The government and development organizations should focus on developing supportive programs and policies to reduce economic vulnerability as well as to develop entrepreneurial competencies.